ANALYSIS OF MINERALOGICAL COMPOSITION OF SOIL AND LAEVISTROMBUS CANARIUM FOR SUSTAINABLE AGRICULTURE ON BATAM ISLAND - Budiana, Budiana; Fahruzi, Iman; Mutialif Maulidiah, Hana; Mishthafiyatillah , Mishthafiyatillah; Dwijotomo, Abdurahman; Kaisar Wisnu Kita, Lalu; Gustin, Oktavianto; Fitriana, Fitriana; Hartanti, Tri; Kharisma Nugraha, Tegar (Departemen Tanah, Fakultas Bio-industri Pertanian dan Kehutanan, Universitas Brawijaya, 2026)
Research on the identification of soil composition and Laevistrombus canarium (Gonggong) composition has been successfully conducted. Identification testing for all samples was performed using XRD and XRF. Diffraction data analysis was carried out using match!2 software and quantitative analysis was conducted using Rietveld refinement. The study found that, using XRF, the main soil constituent is Si and the main Gonggong constituent is Ca. The phases identified using Match!2 software in the soil samples were Quartz, Osumilete and Biotite. Furthermore, the phase identified in the Gonggong sample was CaCO3 single phase. Finally, the study found that the soil tested lacked macronutrients, such as N, needed for plants to grow well. To obtain these macronutrients, Laevistrombus canarium (Gonggong) has potential as an additional soil amendment to improve soil fertility. The implication is that the land in Batam has the potential for sustainable agriculture.